Analisis Pengaruh Kesadaran Halal Dan Gaya Hidup Terhadap Keputusan Pembelian Gokana Ramen Dan Teppan - Hafizah, Nadia Nur; Nur, Mawardi; Syahbudin, Fahmi (Journal of Islamic Economics, Banking, and Social Finance, 2025)
This study investigates the impact of halal awareness and lifestyle on purchasing decisions for Gokana Ramen and Teppan products in Depok City. Utilizing a quantitative approach, the research examines how the variables of halal awareness and lifestyle influence consumer purchasing decisions. The study employs random sampling and quantitative data analysis conducted with SmartPLS 3.2.9. The population consists of Muslim consumers of Gokana Ramen and Teppan in Depok City, with a sample size of 150 respondents. The findings reveal the following: first, halal awareness has a significant effect on purchasing decisions, as indicated by a T-statistic value of 2.3281.96 and a P-value of 0.0200.05; second, lifestyle also significantly affects purchasing decisions, with a T-statistic value of 9.4121.96 and a P-value of 0.0000.05; third, halal awareness and lifestyle together have a significant simultaneous influence on purchasing decisions, evidenced by a T-statistic value of 6.7281.96 and a P-value of 0.0000.05. These results demonstrate that halal awareness and lifestyle significantly impact purchasing decisions, both individually and collectively, for Gokana Ramen and Teppan products in Depok City.